(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In the article the scientific achievements of I. Vernadsky in the field of history of economic pupil are considered, from the emergence of economic knowledge, sights, theories, concepts, the origin of economic science and by the end of XIX century. Two main directions of development of economic science are defined: positive and negative. The history of economic pupil as an organic component of all economic science in close relationship with other concrete economic sciences is considered, the country and time when historical and economic doctrines appeared as independent sphere of science. It was established that I. Vernadsky initiated Scientific school on studying the history of economic pupil in Ukraine. The history of economic thought of Ukraine was not investigated. The names of many scholars-economists have been silent or forgotten, often for political reasons. If the scientific achievements are placed mainly in the movement of opposition Marxist-Lenskoyi methodology in compliance with the principles of mass and partisanship. Ignored, prohibited national aspect of research. The purpose of the work is: to examine the classification of schools, theories, concepts and trends of economic science, to divide them into periods, made a scholar from antiquity and to the end of XIX century.; define trends, characters and content of further development of economic of science, including history of economic thought by the researcher; To find out the theoretical and methodological methods used in the study of interrelations of historical and economic science with other branches of knowledge; Show the contribution of Vernadsky in the development of national and world economic Science in the field of economic student history.